In Vitro Antidiabetic Evaluation and Wound Healing Activity of Root Bark Extracts of Gardenia angustifolia in Streptozotocin-induced Diabetic Rats: Antidiabetic and Wound Healing Activity in Diabetic Rats - Sule, Fatima; Omale, James; Olajide, Joseph (Iranian Journal of Pharmaceutical Sciences, 2025)
This research investigates the glucose-lowering activity and wound-healing effect of the methanol extract of G. angustifolia root bark (MEGR) and ethyl acetate extract of G. angustifolia root bark (EAGR) on streptozotocin-induced diabetic rats. Qualitative phytochemical analysis of the extracts was conducted according to standard procedures. The glucose-lowering ability of the extracts was assayed by in vitro inhibition of α-amylase and α-glucosidase activities. The excisional wound was adopted to evaluate the tissue repair ability of the extracts on diabetic rats. The qualitative phytochemical test identified alkaloids, flavonoids, saponins, total phenols, terpenoids, tannins, and cardiac glycosides in EAGR. The MEGR contains all the aforementioned phytochemicals except tannins and terpenoids. Glucose lowering ability of the extracts studied in vitro shows that with a significantly lower (p < 0.05) IC50 value (34.54 ± 1.31 µg/mL), EAGR has a higher ability to impair the activity of α–glucosidase compared to MEGR (54.03 ± 1.31 µg/mL). Furthermore, with IC50 values of 119.59 ± 1.20 µg/mL and 128.13 ± 0.35 µg/mL for EAGR and MEGR, respectively, there is no significant difference (p > 0.05) in the ability of both extracts to impair α-amylase activity. On the 20th day post-wounding, ointment formulation from the extracts improved the tissue repair process by promoting the wound contraction rate with a percentage of 81.09 ± 1.24 % and 79.92 ± 1.64 % for EAGR and MEGR treated groups, respectively. Furthermore, the total protein content of regenerating tissues was significantly improved (p < 0.05) in the groups treated with EAGR and MEGR, respectively (1.60 ± 0.12 mg/g and 1.57 ± 0.14 mg/g) compared to the diabetic control group (0.68±0.04 mg/g). The ointment formulation from the EAGR and MEGR significantly decreased the period of epithelialization (21.50 ± 0.50 days and 22.25 ± 0.85 days, respectively) compared to the diabetic control group (30.50 ± 0.50 days). The time taken for 50% wound closure was 11.72 days and 12.54 days for groups treated with EAGR and MEGR, respectively. This indicates a shorter time than the diabetic control group (21.24 days). In conclusion, this research indicates the glucose-lowering effect of MEGR and EAGR by impairing the activities of α-amylase and α-glucosidase. Furthermore, the extracts can promote the tissue repair process in the excision wound model of diabetic rats.